2013
DOI: 10.4236/ajps.2013.46145
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Responses of Switchgrass Ecotypes to Temperature

Abstract: Varietal differences of switchgrass in growth and development, biomass yield and partitioning in response to temperature are not well documented. A study was conducted to quantify the effect of temperature on growth, development, and feedstock quality of switchgrass cultivars, and to determine differences between upland and lowland switchgrass. Two lowland ("Alamo" and "Kanlow") and two upland ("Caddo" and "Cave-in-Rock") cultivars of switchgrass were grown in pots filled with pure, fine sand in growth chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…The greater LAI in 2012 might be the result of higher temperatures during early growth periods, which also decreased the LAI differences among upland and lowland ecotypes. These results are in agreement with previous research that switchgrass leaf/stem ratio increases at higher temperatures in both upland and lowland ecotypes [51]. However, in 2013, clear differences between upland and lowland switchgrass varieties for their LAI throughout the growing season occurred, clearly indicating an ecotypic effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The greater LAI in 2012 might be the result of higher temperatures during early growth periods, which also decreased the LAI differences among upland and lowland ecotypes. These results are in agreement with previous research that switchgrass leaf/stem ratio increases at higher temperatures in both upland and lowland ecotypes [51]. However, in 2013, clear differences between upland and lowland switchgrass varieties for their LAI throughout the growing season occurred, clearly indicating an ecotypic effect.…”
Section: Discussionsupporting
confidence: 93%
“…This might be explained by the fact that at higher temperatures switchgrass varieties produced greater tiller numbers in 2012, and resulted in higher DMY than 2013. Kandel et al [51] reported similar findings that at higher temperatures root/shoot and leaf/stem ratios increase in both upland and lowland ecotypes. Biomass yields of switchgrass ecotypes increased in a somewhat linear manner as the growing season progressed in both years.…”
Section: Discussionmentioning
confidence: 64%
“…The strong repression of the genes involved in glucose metabolism strongly supports the significant reduction reported in the cellulose and hemicellulose levels in response to heat stress in switchgrass cultivars [27]. The down regulation of metabolism in general, nitrogen and phosphorus metabolism in particular will have pronounced impact on vegetative growth (Figure 1).…”
Section: Resultssupporting
confidence: 70%
“…S4-S6). Another study documented similar leaf area decline under high temperatures for switchgrass [28]. Additionally, during the high temperature period, we observed that switchgrass leaves rolled causing a possible under-measurement of LAI in the experimental data collected by a ceptometer.…”
Section: Discussionsupporting
confidence: 70%